(untitled) (Colombia Medica, 2012)
Objective: Determine the activity of cortisol in rats treated with exogenous adrenocorticotropic hormone (ACTH) and a resveratrol supplement. Methods: Forty-eight adult male rats and 16 adult female rats (Rattus norvegicus) three months old with a body weight of 200 to 250 g and 300 to 350 g for both male and female were used and kept in controlled environmental conditions, temperature of 20±2° C and light-dark cycles of 14 and 10 hours. They were fed with balanced food and had free access to water. The rats were randomly divided into four groups: group 1, was treated with 5 μg/kg of ACTH i.p. every twelve hours; group 2, received the same treatment with ACTH plus a grape extract supplementation of 40 mg/kg; group 3, only received grape extract and group 4,served as control and only received saline solution (0.9%) i.p. The experimental was designed as a 2×2 factorial with two ACTH levels and two extract grape levels. Results: Significant differences were not found in cortisol concentrations for day, gender or treatment effects (0.75 μg/dL ± 0.11; p <0.001). Conclusion: Results suggest that chronic stress and consume of resveratrol did not produce any effect in the activity of plasmatic cortisol, in stressed and unstressed rats stressed. In the same way, possibly, dose of ACTH did not produce stimulation of the suprarenal gland for these animals.